Respuesta :

Given:

The function is [tex]f(x)=3(x+7)^{\frac{1}{4}}[/tex].

To find:

The function [tex]f^{-1}(x)[/tex].

Solution:

We have,

[tex]f(x)=3(x+7)^{\frac{1}{4}}[/tex]

Substitute f(x)=y.

[tex]y=3(x+7)^{\frac{1}{4}}[/tex]

Interchange x and y.

[tex]x=3(y+7)^{\frac{1}{4}}[/tex]

Divide both sides by 3.

[tex]\dfrac{x}{3}=(y+7)^{\frac{1}{4}}[/tex]

Taking power 4 on both sides.

[tex]\left(\dfrac{x}{3}\right)^4=y+7[/tex]

Subtract 7 from both sides.

[tex]\left(\dfrac{x}{3}\right)^4-7=y[/tex]

[tex]y=\left(\dfrac{x}{3}\right)^4-7[/tex]

Substitute [tex]y=f^{-1}(x)[/tex].

[tex]f^{-1}(x)=\left(\dfrac{x}{3}\right)^4-7[/tex]

Therefore, the correct option is C.